Accuracy, inter‐ and intrarater reliability, and user‐experience of high tibial osteotomy angle measurements for preoperative planning: manual planning PACS versus semi‐automatic software programs - Iris E. W. G. Laven; Femke F. Schröder; Feike deGraaff; J. Christiaan Rompen; Roy A. G. Hoogeslag; Albert H. vanHouten (Journal of Experimental Orthopaedics)
Abstract Purpose To compare the accuracy, inter‐ and intrarater reliability, and user‐experience of manual and semi‐automatic preoperative leg‐alignment measurement planning software for high tibial osteotomy (HTO). Methods Thirty patients (31 lower limbs) who underwent a medial opening wedge HTO between 2017 and 2019 were retrospectively included. The mechanical lateral distal femur angle (mLDFA), mechanical medial proximal tibial angle (mMPTA), and planned correction angle were measured on preoperative long‐leg full weight‐bearing radiographs utilising PACS Jivex Review® v5.2 manual and TraumaCad® v2.4 semi‐automatic planning software. Independent measurements were performed by four raters. Two raters repeated the measurements. Accuracy in the standard error of measurement (SEM), inter‐ and intrarater reliability, and user‐experience were analysed. Additionally, measurements errors of more than 3° were remeasured and reanalysed. Results The SEMs of all measured varus malalignment angles and planned correction angle were within 0.8° of accuracy for both software programs. Measurements utilising the manual software demonstrated moderate interrater intraclass correlation coefficient (ICC)‐values for the mLDFA and mMPTA, and an excellent interrater ICC‐value for the correction angle (0.810, 0.779, and 0.981, respectively). Measurements utilising the semi‐automatic software indicated excellent interrater ICC‐values for the mLDFA, mMPTA, and correction angle (0.980, 0.909, and 0.989, respectively). The intrarater reliability varied substantially per angle, presenting excellent intrarater agreements by both raters (ICC >  0.900) for the correction angle in each software program as well as poor‐to‐excellent ICC‐values for the mLDFA (0.282–0.951 and 0.316–0.926) and mMPTA (0.893–0.934 and 0.594–0.941) in both the manual planning and semi‐automatic software. Regarding user‐experience, semi‐automatic software was preferred by two raters, while the other two raters had no distinctive preference. After remeasurement of five outliers, excellent interrater ICC‐values were found for the mLDFA (0.913) and mMPTA (0.957). Conclusions Semi‐automatic software outperforms the manual software when user‐experience and outliers are considered. However, both software programs provide similar performance after remeasurement of the human‐related erroneous outliers. For clinical practice, both programs can be utilised for HTO planning. Level of evidence Diagnostic study, Level III.